G.E. Moore's ethical theory: Resistance and reconciliation - Hutchinson, Brian (Cambridge University, 2013)
This is a comprehensive study of the ethics of G.E. Moore. Moore's ethical project, set out in his seminal text Principia Ethica, is to preserve common moral insight from skepticism and, in effect, persuade his readers to accept the objective character of goodness. Brian Hutchinson explores Moore's arguments in detail and in the process relates the ethical thought to Moore's anti-skeptical epistemology."--Jacket.